2017
DOI: 10.22159/ajpcr.2017.v10i9.19799
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Profile and Outcome of Neonates Admitted to a Secondary-Level Neonatal Intensive Care Unit in North India

Abstract: Objectives: The objective of this study was to evaluate the performance of a secondary-level neonatal intensive care unit (NICU). Methods:A total of 336 neonates were enrolled in the study. Their clinical profiles at admission and final outcomes were recorded in a predesigned pro forma.Results: Hyperbilirubinemia, sepsis, and perinatal asphyxia were the most common reasons for admission. Eighty-five percentage of the neonates could be managed in secondary-level newborn unit with comparable mortality and mortal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
2
0
0
Order By: Relevance
“…[9,12] It indicates that neonatal low birth weight and pre-term deliveries are one of the common indications for SNCU admission. Neonatal jaundice (53.3%), respiratory distress (22.8%) and sepsis (19.4%)%) were the major reasons for admission in accordance to study by Yusuf et al [13] While, Modi and Kirubakaran [9] reported the sepsis (23.7%), asphyxia (5.3%), pre-term delivery (14.2%) and jaundice (13.4%) as the major reasons for admission. [13,14] Sepsis was found more in out born babies (16,27.1% of total out born babies) compared to inborn ones (4, 8.6% of total inborn).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…[9,12] It indicates that neonatal low birth weight and pre-term deliveries are one of the common indications for SNCU admission. Neonatal jaundice (53.3%), respiratory distress (22.8%) and sepsis (19.4%)%) were the major reasons for admission in accordance to study by Yusuf et al [13] While, Modi and Kirubakaran [9] reported the sepsis (23.7%), asphyxia (5.3%), pre-term delivery (14.2%) and jaundice (13.4%) as the major reasons for admission. [13,14] Sepsis was found more in out born babies (16,27.1% of total out born babies) compared to inborn ones (4, 8.6% of total inborn).…”
Section: Discussionsupporting
confidence: 84%
“…Neonatal jaundice (53.3%), respiratory distress (22.8%) and sepsis (19.4%)%) were the major reasons for admission in accordance to study by Yusuf et al [13] While, Modi and Kirubakaran [9] reported the sepsis (23.7%), asphyxia (5.3%), pre-term delivery (14.2%) and jaundice (13.4%) as the major reasons for admission. [13,14] Sepsis was found more in out born babies (16,27.1% of total out born babies) compared to inborn ones (4, 8.6% of total inborn). This indicates unhygienic deliveries either by unskilled person at septic places or baby's exposure to infections during transport or referral.…”
Section: Discussionsupporting
confidence: 84%